2020
DOI: 10.1007/978-3-030-58201-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of the Balance Discovery Attack on Lightning Network Payment Channels

Abstract: The Lighting Network (LN) is a network of micropayment channels that runs on top of Bitcoin. The balances of payment channels are not broadcasted to the LN network to preserve the privacy of the nodes participating in the network. A balance disclosure attack (BDA) has been proven to be successful in determining the balance of large amounts of channels in the network. In this paper we propose an improved algorithm for the BDA as well as a new type of attack that leverages the differences between LN client softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The LN has been shown to exhibit multiple privacy weaknesses due to statistical hints [8], on-chain footprint [18,31], timing measurements [25], and other attack vectors [13,16,19,32,33,35]. Most relevant to this work, adversarial probing of channel balances has been initially introduced in [11] and unproved upon in [12,17,36] We use a method close to the one of [34], supporting precise error handling for multi-hop payments. We note that channel probing is not necessarily adversarial: nodes, in fact, probe paths in the course of normal payments.…”
Section: Related Workmentioning
confidence: 99%
“…The LN has been shown to exhibit multiple privacy weaknesses due to statistical hints [8], on-chain footprint [18,31], timing measurements [25], and other attack vectors [13,16,19,32,33,35]. Most relevant to this work, adversarial probing of channel balances has been initially introduced in [11] and unproved upon in [12,17,36] We use a method close to the one of [34], supporting precise error handling for multi-hop payments. We note that channel probing is not necessarily adversarial: nodes, in fact, probe paths in the course of normal payments.…”
Section: Related Workmentioning
confidence: 99%
“…The network aims to keep nodes' balances private, and therefore a channel's exact balance is never announced. Several methods to deduce the exact balance of a channel have been suggested [13,31,33]. The main technique is to request a payment via the channel, then, based on whether the payment succeeds to traverse the channel or not, the sender learns whether the balance is greater or smaller than the requested payment amount.…”
Section: Related Workmentioning
confidence: 99%
“…Tochner et al showed that the routing algorithms employed by PCNs may be manipulated to in order to facilitate inclusion of a malicious node in the payment path, thereby increasing the danger of denial-ofservice attacks [50]. Furthermore, recent entries have discussed the possibility of discovering the private channel balances by probing [21,52] and analyzed how much privacy could be retained, if noisy channel balances were to be made public [48]. A number of papers analyzed the graph-theoretic properties of the Lightning Network graph and discussed possible consequences regarding decentralization and routing [25,44,47], as well as graph-based privacy properties [31].…”
Section: Related Workmentioning
confidence: 99%